Surface wave analysis for near surface applications - Dal Moro, Giancarlo 1969- (Elsevier, 2015)
Seismic Wave Analysis for Near Surface Applications presents the foundational tools necessary to properly analyze surface waves acquired according to both active and passive techniques. Applications range from seismic hazard studies, geotechnical surveys and the exploration of extra-terrestrial bodies. Surface waves have become critical to near-surface geophysics both for geotechnical goals and seismic-hazard studies. Included in this book are the related theories, approaches and applications which the lead editor has assembled from a range of authored contributions carefully selected from the latest developments in research. A unique blend of theory and practice, the book’s concepts are based on exhaustive field research conducted over the past decade from the world’s leading seismologists and geophysicists.--Provided by publisher.